ปัจจัยคัดสรรที่มีความสัมพันธ์กับความวิตกกังวลของผู้สูงอายุโรคต้อหิน - วาสนา ฟุ้งฟู (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purposes of this descriptive research were to study the anxiety of older persons with glaucoma and to investigate the relationships between age, sex, level of education, income, visual acuity, length of illness, numbers of other chronic illnesses, activity of daily living, social support, self esteem and anxiety of older persons with glaucoma. Subject consisted of 160 older persons with glaucoma at glaucoma clinic in Rachavithee Hospital, Ramathibodi Hospital and the King Mongkutklao Hospital, and were selected by using multi-stage sampling technique. Research instruments were demographic questionnaires, Barthel ADL Index, social support, self esteem and anxiety questionnaires which were tested for content validity and reliability. The reliabilities of social support, self esteem, and anxiety questionnaires were .863, .865 and .983 respectively. Data were analysed by using SPSS for Windows Version 13, including frequency, mean, standard deviation, Contingency Coefficient, Chi Square Test and Pearson s Product Moment Correlation Coefficient. Major findings were as follows: 1. Anxiety of the older persons with glaucoma was at medium level ([X-bar] = 2.65). 2. income, number of other chronic illness, activity of daily living and social support were significantly negative correlated with anxiety of the older persons with glaucoma, at low level of .05 (r = -.186, -.277, -.245, -.273, respectively). 3. Self esteem was significantly negative correlated with anxiety of the older persons with glaucoma, at medium level of .05 (r = -.586). 4. Level of education and visual acuity were significantly correlated with anxiety of the older persons with glaucoma, at level of .05 (c = .05, and .03, respectively). 5. Age, sex and length of illness were not correlated with anxiety of the older persons with glaucoma